The Basque Country: the heart of Spain, a part of Spain, or Somewhere Else Altogether - Paddy Woodworth (Studies in 20th & 21st Century Literature, 2009)
The Basque Country exhibits contradictory symptoms of good health and chronic internal rupture. A flexible and robust economy and a vibrant cultural life are undermined by opposed senses of identity, which make almost any statement about the region deeply contentious. The verifiability—or otherwise—of Basque nationalist and Spanish nationalist readings of Basque history and culture matter less today than the fact that they are held with genuine conviction by big sectors of Basque society. Both traditions have their own legitimacy, but neither has been capable of fully acknowledging or including the other. Paradoxically, Francoism reinforced Basque nationalist identity, and anxieties about the survival of the Basque language stimulated radical Basque nationalism, with enduring consequences. An accommodation might be found in acceptance by both sides that Basque identities are multiple, and through recognition that there are several ways of being Basque, none of which need negate any of the others. The recent Irish settlement offers some pointers, though no rigid templates. Bernardo Atxaga’s declaration that Euskera is not the Basque language, but a Basque language, is an indication that this process of respecting multiple identities is already underway, though the obstacles to a resolution remain formidable.
Keywords: Basque Country; Euskera; identity; Spain; Francoism; nationalist identity; multiple identities